Microscopic evidence supports the hypothesis of high cellulose degradation capacity by the symbiotic fungus of leaf-cutting ants - Nagamoto, Nilson S. [UNESP] (2011)
Leaf-cutting ants (Hymenoptera, Formicidae) use fresh leaf fragments to cultivate a symbiotic fungus (Basidiomycota, Agaricales) as their food source. There are three hypothetical propositions for the degree of cellulose degradation capacity of this symbiont: (i) that it is high, rendering this polymer an important energy source, as originally purposed by Martin and Weber; (ii) that it is very small, and only facilitates the symbiont to use other cell nutrients and, (iii) that this fungus is metabolically inept against this polymer. The two latter proposals are more recent than the first one but are based on in vitro or highly indirect evidence. Consequently, we carried out a new evaluation of the degradation capability of this fungus, utilizing as realistic an approach as possible by assessing the microscopic effect of fungus cultivation on the leaf anatomy of the grass Paspalum notatum within colonies of the grass-cutting ant Atta capiguara. We observed a complete degradation of the most abundant leaf cells (the non-lignified ones). on the other hand, since lignin-rich structures presented only slight damage, the leaf format was maintained. Therefore, this in vivo study corroborates Martin and Weber's hypothetical proposition: that cellulose is highly degraded by the leaf-cutting ant symbiont, thus serving as an important energy source.